Ambient-cured geopolymer mortars prepared with waste-based sands: Mechanical and durability-related properties and microstructure. (1st March 2019) - Gholampour, Aliakbar; Ho, Van Dac; Ozbakkaloglu, Togay
Abstract: In recent years, the use of industrial by-products and waste-based materials in the construction industry has received significant attention to develop eco-friendly and greener construction materials with the aim of reducing the impact of construction industry on the environment. The development of new concretes where cement is replaced with industrial by-products, such as ground granulated blast furnace slag (GGBS) and fly ash (FA), and natural sand (NS) is replaced with waste-based sands, such as lead smelter slag (LSS) and glass sand (GS), would lead to enormous environmental and health benefits by enabling the use of abundant wastes, reducing the extraction of non-renewable natural resources, and reducing the CO2 emissions associated with concrete production. This paper presents an experimental study on the properties of geopolymer mortars prepared with FA/GGBS, LSS, and GS under ambient curing condition. A total of 12 batches of geopolymer mortars were manufactured and experimental tests were conducted to determine the flowability, hardened density, compressive strength, direct tensile strength, water absorption, and drying shrinkage of each batch together with the alkali-silica reaction (ASR) expansion of batches containing GS. Microstructural analysis was undertaken to describe the reasons for the obtained experimental results. The results show that the compressive and tensile strength of geopolymer mortars increase with an increase in the amount of GGBS. The results also show that an increase in the GGBS amount leads to a decrease in the water absorption of geopolymer mortars. Owing to the lower void amount at the binder-sand interaction zones, LSS- and GS-based geopolymer mortars containing up to 50% GGBS exhibit superior mechanical properties compared to those of their NS-based counterparts. These highly promising findings suggest that the full replacement of NS by LSS and GS can provide an attractive avenue to reduce the environmental impact of abundant waste products and conserve non-renewable natural resources.